THE NORMALIZATION OF TURKEY–SAUDI ARABIA RELATIONS IN THE ERDOĞAN ERA: STRATEGIC INTERESTS AND INTERNATIONAL RESPONSES - Muhammad Hayyi Lana Alkhan; Ahmad Fauzi; Aning Kesuma Putri (Arabic Literature Department, 2025)
The relationship between Turkey and Saudi Arabia has undergone a significant transformation in recent years, particularly under the leadership of President Recep Tayyip Erdoğan. This article seeks to analyze the underlying factors behind the normalization process between the two countries, considering not only political, economic, and security dimensions but also the often-overlooked ideological aspect. Historically, Turkey and Saudi Arabia have maintained opposing ideological stances, particularly regarding their positions on Islamist movements such as the Muslim Brotherhood. This study employs a qualitative methodology based on a comprehensive literature review and secondary data analysis. The findings indicate that the normalization is driven by multiple factors, including political alignment, ideological recalibration, economic interests, and security concerns. Moreover, international responses to this normalization have been mixed, with some countries expressing support while others remain critica.